2011
DOI: 10.1136/bjsports-2011-090009
|View full text |Cite
|
Sign up to set email alerts
|

Exercise during pregnancy improves maternal glucose screen at 24–28 weeks: a randomised controlled trial

Abstract: ObjectiveThe infl uence of an exercise programme performed by healthy pregnant women on maternal glucose tolerance was studied. Study design A physical activity (PA, land/aquatic activities) programme during the entire pregnancy (three sessions per week) was conducted by a qualifi ed instructor. 83 healthy pregnant women were randomly assigned to either an exercise group (EG, n=40) or a control (CG, n=43) group. 50 g maternal glucose screen (MGS), maternal weight gain and several pregnancy outcomes were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
259
0
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(276 citation statements)
references
References 45 publications
4
259
0
13
Order By: Relevance
“…[28][29][30][31][32][33][34][35][36][37][38] Reasons for refusal to provide IPD included lack of time, 39,40 problems with data sharing 41 and conflicts of interest. 42,43 Data were lost in two trials. 44,45 Sixteen randomised controlled trials (RCTs) (including 2265 women) were identified too late in the project to be analysed, and thus we refrained from approaching the authors.…”
Section: Network Meta-analysismentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36][37][38] Reasons for refusal to provide IPD included lack of time, 39,40 problems with data sharing 41 and conflicts of interest. 42,43 Data were lost in two trials. 44,45 Sixteen randomised controlled trials (RCTs) (including 2265 women) were identified too late in the project to be analysed, and thus we refrained from approaching the authors.…”
Section: Network Meta-analysismentioning
confidence: 99%
“…Evidence exists that when good adherence to a physical-activity intervention is attained, a positive impact on glucose control is achieved. For example, in 2 studies in which women were randomised to a supervised physical-activity intervention consisting of 3 supervised sessions per week, women in the intervention arm had significantly lower blood glucose levels than women in the control arm at 28 weeks' gestation [29,30]. …”
Section: Interventions To Support Women To Be Physically Active Durinmentioning
confidence: 99%
“…In a previous study, an exercise program for healthy pregnant women consisting of three sessions of aerobics and swimming per week resulted in a decrease in the casual glucose level in the intervention group (20). However, it can be difficult for pregnant women to begin participating in leisure sports because they usually receive a recommendation from their obstetricians to avoid highintensity exercise in order to prevent miscarriage and premature delivery.…”
Section: Discussionmentioning
confidence: 99%